2019
DOI: 10.1016/j.nut.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Update on glucose in critical care

Abstract: The aim of this review is to summarize recent developments on the mechanisms involved in stress hyperglycemia associated with critical illness. Different aspects of the consequences of stress hyperglycemia as well as the therapeutic approaches tested so far are discussed: the physiological regulations of blood glucose, the mechanisms underlying stress hyperglycemia, the clinical associations, and the results of the prospective trials and meta-analyses to be taken into consideration when interpreting the availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 72 publications
0
31
0
1
Order By: Relevance
“…Adequate glycemic control is believed to decrease systemic inflammation, reduce the risk of AKI and need for dialysis, improve the immune response, and attenuate the catabolic effect of stress‐induced hyperglycemia 27,129,133 . Initial studies of tight glycemic control suggested mortality benefit and demonstrated decreases in EGP; however, mortality benefits were not replicated in subsequent studies, potentially because of an increased incidence of hypoglycemia 20,55,128,134,135 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Adequate glycemic control is believed to decrease systemic inflammation, reduce the risk of AKI and need for dialysis, improve the immune response, and attenuate the catabolic effect of stress‐induced hyperglycemia 27,129,133 . Initial studies of tight glycemic control suggested mortality benefit and demonstrated decreases in EGP; however, mortality benefits were not replicated in subsequent studies, potentially because of an increased incidence of hypoglycemia 20,55,128,134,135 …”
Section: Discussionmentioning
confidence: 99%
“…Dysglycemia in critical illness includes hyperglycemia, hypoglycemia, and glycemic variability, all of which are independent risk factors for higher mortality. 20,25,27,28,55,128 Hyperglycemia depresses the immune system, causes osmotic diuresis and electrolyte abnormalities, worsens catabolic thinning of skeletal muscles, and increases risk of infections. 20,22,26,27,128,129 IR and hyperglycemia in critical illness contribute to a positive-feedback loop of metabolic stress and inflammation.…”
Section: Dysglycemia In Critical Illnessmentioning
confidence: 99%
See 3 more Smart Citations